The moderating effect of managerial competence on information and communication technology, access to finance, innovation and agricultural performance - Mayaki, Abubakar (2021)
Agricultural performance is defined as the production of agricultural goods in sufficient quantity to guarantee food security. The agricultural industry has been in a state of crisis owing to a lack of modern farming systems, which has resulted in food scarcity. The study' s primary aim is to investigate the moderating effect of Managerial Competence (MC) on the relationship between Agricultural Performance (AP) and Information and Communication Technology (ICT), Access to Finance (AF), and Innovation (IN). Nigeria's agricultural performance has deteriorated considerably since independence. The study framework was created in accordance with two theories: the Resource-Based View (RBV) and the Technology Acceptance Model (TAM). This study used a quantitative method. The data were gathered using a cross sectional survey technique from registered small and micro farmers operating in Niger state, Nigeria. The sample was chosen using the probabilistic sampling method. We issued 400 surveys and received 375 responses, of which 301 were usable. Both descriptive and inferential analyses used in the study. The findings established a strong and direct connection between AF and IN and AP. Meanwhile, ICT was deemed insignificant. MC also acts as a moderator in the connection between AF and AP, as well as IN and AP. However, it was shown that MC had no effect on the connection between ICT and AP. The findings indicated that AF and IN had a substantial effect on AP. The findings offer critical information for small and micro farmers, the agriculture ministry, policymakers, and academics seeking to improve agricultural performance in Nigeria. Finally, the study's merits, limitations, and recommendations for future research were addressed.